2021
DOI: 10.1371/journal.pone.0251845
|View full text |Cite
|
Sign up to set email alerts
|

Evolving public behavior and attitudes towards COVID-19 and face masks in Taiwan: A social media study

Abstract: Facing the COVID-19 pandemic, Taiwan demonstrated resilience at the initial stage of epidemic prevention, and effectively slowed down its spread. This study aims to document public epidemic awareness of COVID-19 in Taiwan through collecting social media- and Internet-based data, and provide valuable experience of Taiwan’s response to COVID-19, involving citizens, news media, and the government, to aid the public in overcoming COVID-19, or infectious diseases that may emerge in the future. The volume of Google … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…Further negative influences of wearing face masks and the correlation with social anxiety and mental health were identified by Saint and Moscovitch ( 36 ) in their exploratory review. A Taiwanese study by Chin et al ( 37 ) shed light on the importance of fear as a driving factor for the public during the COVID-19 pandemic to adhere to protection measures.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Further negative influences of wearing face masks and the correlation with social anxiety and mental health were identified by Saint and Moscovitch ( 36 ) in their exploratory review. A Taiwanese study by Chin et al ( 37 ) shed light on the importance of fear as a driving factor for the public during the COVID-19 pandemic to adhere to protection measures.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A more thoughtful information process involves systematic processing that relies more on cognitive resources and uses an analytic and in-depth manner to process information, whereas a more superficial information process relies less on cognitive resources but uses a shortcut to process information [ 4 , 18 ]. The RISP model has been applied to examine a variety of risk issues, including obesity [ 19 ], flooding [ 20 ], air pollution [ 21 ], Zika virus [ 22 ], and COVID-19 [ 1 , 23 ].…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…COVID-19 is such an unpredictable disease that when it emerged in Taiwan, people were situated in a highly uncertain context, which prompted people to seek and discuss COVID-19-related information on the internet in great volume. Chin et al [ 21 ] investigated the contents of social media and Google search volume in Taiwan during this time and found that the information from news reports transmitted to the public was instantly transformed into relevant discussions in social media and was also positively correlated with Google search volumes. Various types of information from different sources are available to the public, containing a great deal of misinformation.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Various types of information from different sources are available to the public, containing a great deal of misinformation. During the COVID-19 pandemic, misinformation is rife, which causes distress for most people because misinformation contains rumors, incorrect protective measures, and false disease information [ 3 , 21 ]. If people cannot differentiate true from false information, it may result in detrimental effects on their health.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation